2007
DOI: 10.1111/j.1743-6109.2006.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Function and Activity Following Cystectomy and Continent Urinary Tract Diversion for Benign Indications: A Clinical Pilot Study and Review of Literature

Abstract: Introduction There are limited data on female sexual function after cystectomy for benign indications. Aims To evaluate postoperative sexual items following cystectomy and continent urinary diversion for benign indications (e.g., severe incontinence, interstitial cystitis) in female patients. Furthermore, to review the studies investigating changes in women’s sexual function after cystectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…We utilized the FSFI, a well‐validated and widely used instrument for evaluation of sexual function in women [5,13,14,19,20]. The Chinese version of the FSFI has also been utilized and validated in previous studies [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized the FSFI, a well‐validated and widely used instrument for evaluation of sexual function in women [5,13,14,19,20]. The Chinese version of the FSFI has also been utilized and validated in previous studies [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are worthwhile in comparison with other epidemiological studies, because of the large sample size. We utilized the FSFI, a well-validated and widely used instrument for evaluation of sexual function in women [5,13,14,19,20]. The Chinese version of the FSFI has also been utilized and validated in previous studies [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact was not as pronounced in those women who had undergone orthotopic and nonstomal types of diversions [20]. Comparatively, data from a small retrospective study showed that the majority of women who undergo cystectomy for benign indications tend to have improvement or no change in sexual function postoperatively [21].…”
Section: Etiologymentioning
confidence: 97%
“…Female sexual dysfunction as a clinical term includes a variety of sexual problems. Although 30-50% of women suffer from sexual dysfunction, it was only recently that more medical and clinical researches have focused on the problems related to urologic and gynecologic operations (10,11).…”
Section: Discussionmentioning
confidence: 99%